PENGARUH JOB CHARACTERISTIC, PELATIHAN METODOLOGI PENELITIAN DAN BUDAYA AKADEMIK TERHADAP PRODUKTIVITAS DOSEN DALAM PENELITIAN - R. WASISTO RUSWIDIONO (Jurnal Bisnis dan Akuntansi, 2008)
This Research examines the effect of Job Characteristic, Training on Research Methodology and Academic Culture toward Productivity of Lectures in Research. Data were collected using questioner. The questionnaires were distributed to the full time lecturers at STIE Trisakti, STMT Trisakti and STP Trisakti who chosen randomly. Data were analyzed using multiple regression analysis. The results of the research showes that Academic Culture affects Productivity of Lecturer in Research. On the other hand, Job Charac-teristic and Training on Research Methodology don’t affect the Productivity of Lecturers in Research. Full time lectures will increase their productivities hand in hand with the development and growth of scientific culture in universities and it is called academic culture.